Cross amplification of 16S rRNA bacterial primer 27F/1492R on horticultural crop chloroplast genome - Santosa, Adyatma Irawan; Hilmany, Taufiq; Dewi, Nurul Aulia; Rahmawati, Novianti Ekaputri; Putri, Erika Ananda; Hafidsya, Tiara; Setyaningrum, Ary Virgianti; Dewi, Rulia Ervina; Sari, Gracela Nanda Puspita; Nubatonis, Mars Buwn Fraset Manao; Widyawan, Arya (Agricultural Science, 2024)
Molecular techniques have been applied as fast and accurate detection methods of plant pathogenic bacteria. Bacteria-specific primer 27F paired with the universal primer 1492R was used in PCR to detect plant pathogenic bacteria in symptomatic leaves of tomato (Solanum lycopersicum L.), chili pepper (Capsicum annum L.), napa cabbage (Brassica rapa subsp. pekinensis L.), cabbage (Brassica oleracea var. capitata L.), and longan (Dimocarpus longan Lour.). The targeted single bands with length of 1400 bp were obtained but bidirectional sequencing of the PCR products recovered partial sequence of chloroplast instead of bacterial genomes. Thus, this result confirmed cross amplification of 27F/1492R primer pair against chloroplast genome of plants. Phylogenetic tree was constructed to separate the tested isolates according to their taxonomic relations: Order Sapindales, Solanales, and Brassicales. In-silico analysis on the new five and nineteen selected sequences in NCBI GenBank detected at least seven conserved regions with some single nucleotide polymorphisms. This report might be a cautionary advice for other researchers to avoid false positive results which could lead to misdiagnosis of bacterial plant diseases.